The Sign of Relation and the Challenges of Journalistic Narratives on the LGBT Community - Gonçalves, Gean Oliveira; Medina, Cremilda Celeste de Araújo (Brazilian journalism research, 2018)
In this article, we present the challenges faced by journalists who interviewed lesbians, gays, bisexuals, transgenders and intersexuals (LGBT) to construct narratives and understand the vulnerability that these people must live with, as well as the listening challenges that this process represents. We present a field investigation based on the method of reporting and interview three journalists, understanding their renditions of reports and books they have written on the issue, and elaborating a discussion on the “Sign of Relation”; in other words, how alterity, complexity and complicity can be achieved in journalistic practice; elements that are capable of stimulating authorship and recognizing the differences and inequalities built around gender and sexuality in our societies. No presente texto, apresentamos os desafios de jornalistas que vão ao encontro de lésbicas, gays, bissexuais, travestis, intersexuais e homens e mulheres transexuais (LGBT) para construir narrativas com o devido respeito e compreensão das dimensões de vulnerabilidade em torno da vida dessas pessoas e os desafios de escuta que esse processo representa. Apresentamos uma investida de campo, por meio do método da reportagem, na qual assinalamos as interpretações de três jornalistas sobre seus livros-reportagem com temática LGBT para elaborar uma discussão sobre o “Signo da Relação”, isto é, quais são os caminhos possíveis para alcançar alteridade, complexidade e cumplicidade na prática jornalística, elementos capazes de estimular a autoria e o devido reconhecimento das diferenças e desigualdades construídas em torno do gênero e da sexualidade em nossas sociedades. En este artículo, presentamos los desafíos de periodistas que van al encuentro de lesbianas, gays, bisexuales, travestis, intersexuales y hombres y mujeres transexuales (LGBT) para construir narrativas con el debido respeto y comprensión de las dimensiones de vulnerabilidad alrededor a la vida de esas personas y los desafíos de escucha que este proceso representa. Partimos de una investidura de campo, por medio del método del reportaje, en la que señalamos las interpretaciones de tres periodistas sobre sus libros-reportaje con temática LGBT para elaborar una discusión sobre el “Signo de la Relación”, o sea, cuáles son los caminos posibles para alcanzar alteridad, complejidad y complicidad en la práctica periodística, elementos capaces de estimular la autoría y el debido reconocimiento de las diferencias y desigualdades construidas en torno al género y la sexualidad en nuestras sociedades.